Correlation between body weight and eccentric hamstring strength in american football players - Hacking, T. K.; Wilwand, M.; Johnson, A. W.; Mortensen, B. B. (International Journal of Exercise Science Conference Proceedings, 2025)
Hamstring strength and explosiveness is imperative for collegiate American football players to perform at the highest level. Understanding the respective correlations, based on players positions, between eccentric hamstring strength (HS) and body weight (BW) among football players may help coaches and players to develop strength protocols required for specific positions. We hypothesize that increasing BW will result in increased eccentric HS.